2014
DOI: 10.3390/ijerph110505006
|View full text |Cite
|
Sign up to set email alerts
|

Di-Ethylhexylphthalate (DEHP) Modulates Cell Invasion, Migration and Anchorage Independent Growth through Targeting S100P in LN-229 Glioblastoma Cells

Abstract: Glioblastoma multiforme (GBM) is the most aggressive brain cancer with a median survival of 1–2 years. The treatment of GBM includes surgical resection, radiation and chemotherapy, which minimally extends survival. This poor prognosis necessitates the identification of novel molecular targets associated with glioblastoma. S100P is associated with drug resistance, metastasis, and poor clinical outcomes in many malignancies. The functional role of S100P in glioblastoma has not been fully investigated. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Cell cycle progression is regulated mainly by the tumor suppressor protein (pRb) and transcriptional factor (E2F1) simultaneously. pRb is phosphorylated by nearly 16 residues prominently S608 and T373 by CDKs leading to heteromerization with E2F1 and regulated cancer cells proliferation 8,9,11–14,17–25,38 . ATO has been used successfully for treatment of APL patients by inhibiting APL cells proliferation at higher concentrations 4,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle progression is regulated mainly by the tumor suppressor protein (pRb) and transcriptional factor (E2F1) simultaneously. pRb is phosphorylated by nearly 16 residues prominently S608 and T373 by CDKs leading to heteromerization with E2F1 and regulated cancer cells proliferation 8,9,11–14,17–25,38 . ATO has been used successfully for treatment of APL patients by inhibiting APL cells proliferation at higher concentrations 4,39 .…”
Section: Discussionmentioning
confidence: 99%
“…We made p53 knockdown NB4 cells using lentivirus shRNA (Dharmacon Inc; Lafayette, CO) method as described earlier [ 55 ]. In brief, we seeded 10,000 NB4 cells in 25 µl of transduction medium (RPMI 1640) without serum in each well with polybrene (8 µg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…6a). The studies showed that miR-148a-regulated proteins, such as GADD45A, GRP78, PARK7, and S100P, are invovled in cell-cell adhesion and are associated with the formation and invasion of glioma [25][26][27][28]. In addition, miR-148a also regulates other important biological processes, including apoptosis, DNA repair, mitosis cycle regulation, cell proliferation, nucleosome assembly, nucleocytoplasmic transport, and translational initiation, and these are related to the occurrence and development of cancer.…”
Section: Functional Enrichment Of Mir-148a-regulated Proteinsmentioning
confidence: 99%